Penerapan Hukum Materil terhadap Pelaku Pembunuhan dengan Unsur Penyertaan (Studi Kasus Putusan Mari No. 966 k/pid/2014) - Elfirda Ade Putri (JURNAL MERCATORIA, 2020)
Murder accompanied by inclusion or carried out jointly is a special form of murder that incriminates the perpetrators. Basically, judges 'considerations in deciding cases, especially with murder cases, are sometimes not in accordance with applicable law, apart from that the sentence imposed is sometimes not in accordance with the perpetrators' actions, so that justice is not obtained, especially for the injured parties. There are differences in sentencing in each court, even though prior to sentencing, the judge has considered the same juridical considerations from each court level, whether it consists of indictments of the public prosecutor, defendant's statements, witness statements, witness statements, evidence and articles of law criminal. The application of material law by the Public Prosecutor in the Supreme Court Decision number 966 K / Pid / 2014 is not right. The public prosecutor uses the subsidair indictment using Article 338 paragraph (1) jo Article 55 of the Criminal Code. Public prosecutor did not ensnare the defendant Article Number 340 of the Indonesian Criminal Code, where the criminal act committed by the defendant contained an element of "planning".